2021
DOI: 10.3390/jcm10153323
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Follow-Up of Men with Non-Obstructive Azoospermia Following Testicular Sperm Extraction

Abstract: Testicular sperm extraction (TESE) is a surgical procedure which, combined with intracytoplasmic sperm injection, constitutes the main treatment for achieving biological parenthood for patients with infertility due to non-obstructive azoospermia (NOA). Although it is effective, TESE procedures might cause structural testicular damage leading to Leydig cell dysfunction and, consequently, temporary or even permanent hypogonadism with long-term health consequences. To a lesser extent, the same complications have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It may cause structural testicular damage leading to Leydig cell dysfunction, which is caused by reduced blood supply due to vascular injury and increased intratesticular pressure due to hematoma, and long-term hypogonadism, especially in patients with small testicular volume, such as Klinefelter syndrome. 30 A recent meta-analysis of TESE complications reported that patients with NOA, including Klinefelter syndrome, had the lowest postoperative testosterone levels at 6 months and recovered to baseline levels at 18-26 months 30,31 ; thus, patients may be monitored for approximately 2 years after surgery. To prevent postoperative hypogonadism, the following measures should be considered: minimize the amount of tissue sampling, take maximum care to avoid vascular damage, limit the testicular incision to one side only, and minimize sampling of the second testis if the thickness of the seminiferous tubules is homogenous when bilateral testes are incised.…”
Section: Micro-tesementioning
confidence: 99%
“…It may cause structural testicular damage leading to Leydig cell dysfunction, which is caused by reduced blood supply due to vascular injury and increased intratesticular pressure due to hematoma, and long-term hypogonadism, especially in patients with small testicular volume, such as Klinefelter syndrome. 30 A recent meta-analysis of TESE complications reported that patients with NOA, including Klinefelter syndrome, had the lowest postoperative testosterone levels at 6 months and recovered to baseline levels at 18-26 months 30,31 ; thus, patients may be monitored for approximately 2 years after surgery. To prevent postoperative hypogonadism, the following measures should be considered: minimize the amount of tissue sampling, take maximum care to avoid vascular damage, limit the testicular incision to one side only, and minimize sampling of the second testis if the thickness of the seminiferous tubules is homogenous when bilateral testes are incised.…”
Section: Micro-tesementioning
confidence: 99%
“…Common pathogenic factors include hereditary diseases, congenital testicular abnormalities, pathological changes of the testis, endocrine diseases, radiation, physical, chemical, and pharmaceutical damages [ 5 ]. Removing the obstruction of the vas deferens by microsurgery is the first choice for treatment of OA, while intracytoplasmic sperm injection (ICSI) and testicular sperm extraction (TESE) are more recommended for NOA [ 6 ]. Hence, the differential diagnosis of OA and NOA is of great significance because it is directly related to the choice of treatment methods [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Special Issue in this journal (mdpi.com/journal/jcm/special_issues/NOA_Management) was dedicated to this argument. As more extensively detailed in the accompanying editorial [ 3 ], the Special Issue was built on the contributions of opinion leaders such as Peter N. Schlegel and his group, who illustrated how to manage patients with NOA and optimize the success of mTESE [ 4 ], as well as the reproductive chances of men with NOA according to the underlying etiologies [ 5 ]; Sandro Esteves and coworkers, who provided a detailed explanation on how to discriminate the two forms of azoospermia, obstructive vs. non-obstructive [ 6 ]; Krausz and Cioppi, who reviewed the most common genetic abnormalities in men with NOA and their possible impact on their general and reproductive health, as well as on their offspring health [ 7 ]; Goulis and colleagues, who showed how the eventual post-surgical hypogonadism may depend upon some clinical factors, including etiology of NOA, the number of previous surgical attempts, and testicular volume [ 8 ]; Aydos, who provided an in-depth review of the available procedures to select testicular sperm for ICSI [ 9 ]; Smith, who explored the possible application of microfluidic technology to isolation of sperm from testicular samples [ 10 ]; and our group, who proposed a detailed description of the microTESE surgical technique [ 11 ], reviewed the current evidence about the possible effect of hormonal treatments on the outcome of surgical sperm retrieval [ 12 ], and evaluated the studies attempting to individuate reliable predictors of sperm retrieval outcome [ 13 ].…”
mentioning
confidence: 99%